PONDERING LANGUAGE RIGHTS: A NOVELLA - Oquendo, University of Connecticut-School of Law, Estados Unidos, Angel (Espaço Jurídico Journal of Law [EJJL], 2012)
Abstract: This article maintains that a campaign to exterminate a language cannot but aim at annihilating a community itself. The present piece of fiction might enable the reader effectively to re-imagine discriminatory oppression in the United States. How does U.S. law regulate linguistic practices and cultures? Does it operate explicitly, through the constitutional or statutory officialization of English? This approach will help to underscore how discrimination operates radically differently as provincialism, as subordination, and as colonialism. One would then fully visualize why the struggle for liberation must, alternatively and depending on the context, extol the virtues of pluralism, combat social subjugation, and pursue decolonization. Latin@ characters could vividly show how their community faces and fights against colonial domination. Most groups identify staunchly with and often define who they are through their tongue. The central argument of this article maintains that an onslaught on a particular language ordinarily emasculates the people who speak it. Keywords: Cultural rights. Language. Discrimination. Community